Lipid Nanoparticulate Drug Delivery Systems: Recent Advances in the Treatment of Skin Disorders - Stefan R. Stefanov; Velichka Y. Andonova (MDPI AG, 2021)
The multifunctional role of the human skin is well known. It acts as a sensory and immune organ that protects the human body from harmful environmental impacts such as chemical, mechanical, and physical threats, reduces UV radiation effects, prevents moisture loss, and helps thermoregulation. In this regard, skin disorders related to skin integrity require adequate treatment. Lipid nanoparticles (LN) are recognized as promising drug delivery systems (DDS) in treating skin disorders. Solid lipid nanoparticles (SLN) together with nanostructured lipid carriers (NLC) exhibit excellent tolerability as these are produced from physiological and biodegradable lipids. Moreover, LN applied to the skin can improve stability, drug targeting, occlusion, penetration enhancement, and increased skin hydration compared with other drug nanocarriers. Furthermore, the features of LN can be enhanced by inclusion in suitable bases such as creams, ointments, gels (i.e., hydrogel, emulgel, bigel), lotions, etc. This review focuses on recent developments in lipid nanoparticle systems and their application to treating skin diseases. We point out and consider the reasons for their creation, pay attention to their advantages and disadvantages, list the main production techniques for obtaining them, and examine the place assigned to them in solving the problems caused by skin disorders.